Changes in the Spatial Development of a Satellite Town under the Impact of a Metropolitan City—Evidence from Pruszcz Gdański (Poland) - Anna Świątkiewicz (Land, 2021)
Nowadays, large cities are becoming troublesome to live in in many respects. Due to the high prices of real estate, they are not attractive to young people. The literature often presents analyses of the phenomenon of urban sprawl to suburbia, but the subject of the impact of a metropolitan city on the functioning and changes in spatial development of satellite towns is rarely discussed. This study attempts to describe and to determine factors conducive to this process by identifying, through participant observation, the potential phenomenon of the influence of Gdańsk as a city with metropolitan functions on Pruszcz Gdański, a town directly adjacent to it. The article uses two main groups of methods: (a) a comparative analysis of orthophotomaps from 2005–2020 which allowed for recreating the dynamics of housing development, supported by land mapping as part of field research; (b) a structured internet survey on a sample of 393 residents which allowed identifying the factors influencing the spatial development of Pruszcz Gdański and the perception of this phenomenon, as well as an in-depth interview with a group of 6 residents which allowed obtaining detailed information on the quality of life in Pruszcz Gdański and the factors that determine living in this town. The proximity of both cities and much lower real estate prices in Pruszcz Gdański, which still has most of the functions of an independent town, is beneficial to settling down of migrants from the core of the metropolis. This process particularly applies to young people of working age who cannot afford to buy a new flat in Gdańsk. Building new multi-family housing estates close to the border with Gdańsk has created a kind of new service band or, in a sense, a “town within a town”.